DESKRIPSI PEMAHAMAN KONSEP SISWA PADA MATERI LAJU REAKSI - Marthafera, Prisila; Melati, Husna Amalya; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aims of this study were to describe the ability and factors affecting students? conceptual understanding on material of reaction rate. The method of this research was descriptive research. The subjects in this study were 27 students of class XI IPA SMAS Kristen Setia Putussibau. Test of conceptual understanding and interviews guidelines were used to collect the data. The results showed that the percentage of describing the meaning of the reaction rate, determining the reaction order, determining the rate equation, determining the reaction rate constant, determining the price of the reaction rate and explaining the factors that effect the reaction rate based on successive collision theory were 31%, 45%, 41%, 22%, 24%, and 35% respectively. According to interviews, there were two factors that affect students conceptual understanding wich are individual factors were consist of exercise intelligence and motivation, and the social factors were consist of teachers and teaching methods, tools used in learning and family. Social factors become the largest average percentage of students conceptual understanding affect as many as 42%.Keywords: Description, Concept understanding, The reaction rate, Social factors